MUSEUM DIRGANTARA ADISUCIPTO YOGYAKARTA DENGAN PENDEKATAN ARSITEKTUR FUTURISTIK Landasan Konseptual Perencanaan dan Perancangan - , PUTRI ANGGITA MUSTIKASARI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Indonesia as a developing country, is sometimes being underestimated by itâs own nation. The lack of nationalism and people awareness of change will only make it worse. Therefore, museum has a very important role to show a country proud history and to form future pioneers. Many people donât know about the fact that Indonesian military force has ever been one of the biggest and strongest around the world. On 1960, Indonesian Air Force was one of the most lethal air force. With Uni Sovyet support, Indonesia had had military aircrafts which using the same technology as big country like The US, Russia, and Britain. On the top of that, Indonesian Aerospace (PT Dirgantara Indonesia) used to be the first and the only aerospace company in South-East Asia. As a matter of fact, it was the most succesfull aerospace company in developing countries. It all begins from the previous facts that are needed to be informed to society, Air and Space Museum becomes one of the most significant agent to shape people understanding concerning to Indonesia aviation world. Futuristic architecture approach is used for a reminder to society that Indonesia isnât as conservative as people think. Based on that approach, a concept will be discovered, which then will become the guidance to design the space until this museum will come out as the only education facility that is not only teaching history, but also a place where people could learn anything about science and technology in Indonesian aviation.